The Influence of Parent-Child Attachment and Peer Attachment on Adolescent Aggressive Behavior - Wati, Risa Novia; Setiawati, Farida Agus; Kay Leng, See Too (Universitas Ahmad Dahlan, 2024)
This study aims to determine the role of parent-child attachment and peer attachment on adolescent aggressive behavior. This research is quantitative research. The study population was private high school students in East Mesuji. Using the Krejcie and Morgan formula, a sample of 113 students was selected. Data were collected with three scales, namely the parent-child attachment scale, peer attachment, and aggressive behavior. Subject responses were analyzed using SPSS version 25 and analyzed with multiple linear regression models, stimulant testing (F test) resulted in a significance value of 0.000 (<0.05). Thus, the results of this study indicate that parent-child attachment and peer attachment together have a very significant influence on adolescent aggressive behavior.